2010
DOI: 10.4314/ajfand.v9i7.47682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical and bacteriological quality of raw milk from Neudamm dairy farm in Namibia

Abstract: The quality of raw milk obtained from Friesian (Holstein) cows at Neudamm dairy farm was investigated after the quality issue was raised by some milk consumers at the University of Namibia, Neudamm campus. Some consumers complained about the short shelf-life of the milk as it is sold untreated due to lack of processing facilities at the centre. Others were worried of their health as they usually ferment raw milk for home use. In addition, the farm has no proper records of the quality of its milk for dairy herd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 6 publications
1
21
1
1
Order By: Relevance
“…Mould count in the examined raw milk samples was ranged from 1×10 2 to 6×10 2 cfu/mL with a mean ± SE value of 2.284 ± 0.488 ×10 2 cfu/mL (Table 1). These results are higher than (Desmasures et al, 1997) and (Bille et al, 2009) and lower than (Tasci, 2011).…”
Section: Advances In Animal and Veterinary Sciences February 2016 | Vcontrasting
confidence: 49%
“…Mould count in the examined raw milk samples was ranged from 1×10 2 to 6×10 2 cfu/mL with a mean ± SE value of 2.284 ± 0.488 ×10 2 cfu/mL (Table 1). These results are higher than (Desmasures et al, 1997) and (Bille et al, 2009) and lower than (Tasci, 2011).…”
Section: Advances In Animal and Veterinary Sciences February 2016 | Vcontrasting
confidence: 49%
“…Estudos realizados no Brasil (Cofani dos Santos et al 2009) e na Namíbia (Bille et al 2009) relataram valores de CBT menores em sistemas convencionais, embora Langoni et al (2011) no Brasil, relataram níveis altos de CBT em sistemas orgânicos de produção. Baixa CBT indica boas práticas de ordenha e é um dos principais parâmetros avaliados na mensuração da qualidade do leite (Santos & Fonseca 2007).…”
Section: Contagem Bacteriana Totalunclassified
“…However, it was significantly (P<0.01) affected by stages of lactation. It was less than the finding of Bille, Mirzadeh and Tekelemichael as they reported that, 12.33% in Namibia, 12.57% Lordgan region in Iran and 12.58% in Dire Dawa area, respectively [9][10][11]. According to European Union recognized quality for total solid content of cow's milk not less than 12.5% [13].…”
Section: Total Solid Contentmentioning
confidence: 93%